2018
DOI: 10.1055/a-0801-8771
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Plants Used in South African Traditional Medicine for the Management and Treatment of Hypertension

Abstract: South Africa contains 9% of the worldʼs higher plants, and despite its rich biodiversity, it has one of the highest prevalence of hypertension in Africa. This review provides information on medicinal plants embraced in South Africa for hypertension management, with the aim of reporting pharmacological information on the indigenous use of these plants as antihypertensives. This review not only focuses on the activity of antihypertensive medicinal plants but also reports some of its phytochemical constituents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 91 publications
1
27
0
Order By: Relevance
“…Indications in the context of respiratory conditions. Citrus limon has been used to relieve cough, and as expectorant in bronchitis (Papp et al, 2011;Klimek-Szczykutowicz et al, 2020); and as anti-inflammatory (Parhiz et al, 2015), sore throat (Balogun and Ashafa, 2019).…”
Section: Herbal Remedies Used To Relieve Symptoms Related To Respiratmentioning
confidence: 99%
“…Indications in the context of respiratory conditions. Citrus limon has been used to relieve cough, and as expectorant in bronchitis (Papp et al, 2011;Klimek-Szczykutowicz et al, 2020); and as anti-inflammatory (Parhiz et al, 2015), sore throat (Balogun and Ashafa, 2019).…”
Section: Herbal Remedies Used To Relieve Symptoms Related To Respiratmentioning
confidence: 99%
“…In Romanian traditional medicine, C. limon essential oil was administered on sugar for suppressing coughs [3]. Aside from being rich in vitamin C, which assists in warding off infections, the juice is traditionally used to treat scurvy, sore throats, fevers, rheumatism, high blood pressure, and chest pain [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this ethnopharmacological survey indicate that 15 of the 26 reported species exhibit high RCF values, reflecting the significant consensus among informants about the presumed powerful therapeutic potential of these species [41]. Numerous previous ethnopharmacological studies have shown that all plants of the list are still being used for the treatment of HTN by many communities in different parts of the world [15,28,29,30,34,42,43,44,45,46,47]. In particular, the popular use of some species such as A. ampeloprasum , A. graveolens , C. azarolus , M. longifolia , U. dioica and V. odorata having very high RCF values (0.85–0.10) makes it tempting to speculate that their potential as a valuable source for pharmaceutical novel drug discovery is promising [48,49,50,51,52].…”
Section: Discussionmentioning
confidence: 94%